2020
DOI: 10.1002/ijc.33277
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing the impact of 11 national Be Clear on Cancer public awareness campaigns, England, 2012 to 2016: A synthesis of published evaluation results

Abstract: The Be Clear on Cancer (BCoC) campaigns have run in England since 2010. They aim to raise awareness of possible cancer symptoms, encouraging people to consult a general practice with these symptoms. Our study provides an overview of the impact of 11 national campaigns, for bowel, lung, bladder and kidney, breast and oesophago‐gastric cancers. We synthesised existing results for each campaign covering seven clinical metrics across the patient pathway from primary care attendances to one‐year net survival. For e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 36 publications
(80 reference statements)
3
30
0
Order By: Relevance
“…This campaign was also associated with an increase in the number of patients diagnosed with early-stage LC, and a decrease in cases of advanced LC (Ironmonger et al, 2015). A recent overview of the impact of 11 national 'Be Clear on Cancer' campaigns for various cancers including LC found that these campaigns impacted positively on help seeking by patients and referral patterns by GPs (Lai et al, 2020). It was also found that some campaigns were associated with an increase in cancer diagnoses and higher proportions of cancers diagnosed at early stages (Lai et al, 2020).…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…This campaign was also associated with an increase in the number of patients diagnosed with early-stage LC, and a decrease in cases of advanced LC (Ironmonger et al, 2015). A recent overview of the impact of 11 national 'Be Clear on Cancer' campaigns for various cancers including LC found that these campaigns impacted positively on help seeking by patients and referral patterns by GPs (Lai et al, 2020). It was also found that some campaigns were associated with an increase in cancer diagnoses and higher proportions of cancers diagnosed at early stages (Lai et al, 2020).…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…Although some randomized control trials have been conducted, 120 , 142 the majority of early diagnosis programs are natural experiments and so evaluations more often take other forms such as before and after designs and interrupted time series analysis, commonly involving mixed-methods research. 22 , 25 , 27 , 40 , 135 , 143 - 145 …”
Section: Monitoring and Evaluationmentioning
confidence: 99%
“…For example, a range of process and outcome measures have been examined for the evaluation of the Be Clear on Cancer campaigns in England. 25 These include the cancer referral rate (the number of urgent referrals for suspected cancer made by primary care practices divided by the registered practice population) and referral scheme sensitivity (the number of cancer diagnoses resulting from an urgent referral, rather than another route to diagnosis). The primary care interval (time from first presentation in primary care to referral to secondary care) has also been highlighted as a measure of diagnostic timeliness in England, Scandinavia, and other countries 50 , 147 but is of less relevance to jurisdictions where patients may access specialist care directly.…”
Section: Monitoring and Evaluationmentioning
confidence: 99%
See 2 more Smart Citations